Extracellular matrix modulates exosome secretion in macrophages in fibrotic lungs through the autophagy pathway - Li, Feng (The University of Edinburgh, 2017)
Lung fibrosis is characterised by increased deposition of fibrotic extracellular matrix (ECM) in the lung interstitium causing lung dysfunction. Idiopathic pulmonary fibrosis (IPF) is the most common form of fibrotic interstitial lung diseases. It is believed that the disruption of alveolar homoeostasis and abnormal wound healing drives the lung fibrosis process and leads to a dysregulated chronic fibrotic condition. The macrophage is a key effector cell in normal wound healing and fibrosis. Autophagy is an important mechanism for the maintenance of cellular homoeostasis, however, its role in macrophages and lung fibrosis is largely unknown. ECM has been proposed as an active functional component that regulates cell biology and it can modulate the autophagy process. Modulation of autophagy affects the secretion of exosomes which are mediators of cell-cell communication. Thus, it is hypothesised in this thesis that fibrotic ECM modulates the autophagy pathway in alveolar macrophages (AM) and subsequently affects exosome secretion in the fibrotic lung. In this thesis, I investigated the effect of ECM on macrophage autophagy and the subsequent effect on exosome biology using in vitro models and clinical samples. It was shown that collagen-I, the most common type of increased ECM in IPF, upregulated the basal autophagy pathway in macrophages in that it increased the formation and facilitated the degradation of autophagosomes. It was also shown that there is a blockage of the autophagy pathway and lysosomal dysfunction in AM from the fibrotic lungs (fibrotic AM). ECM derived from IPF lung fibroblasts did not block the autophagy pathway, but it increased both the basal and rapamycin-induced autophagy in macrophages. Modulation of the autophagy pathway in macrophages affected exosome secretion in vitro and fibrotic AM released fewer exosomes ex vivo. BAL fluid exosome levels were significantly lower in fibrotic ILD and low baseline exosome levels in BAL fluid may be associated with progressed IPF. BAL fluid exosomes expressed classic exosome markers but their origin remained unclear because they did not express the typical surface markers of specific cell types. To summarise, this study suggests the normal homeostatic process of autophagy and exosome biosynthesis in AM is subverted in the fibrotic lungs. Fibrotic ECM may exacerbate the impairment of autophagy in the setting of dysfunctional lysosomes which affects exosome secretion and compromises cellular communication and signalling. Thus, normalising the autophagy pathway and restoring the cellular communication via alveolar exosomes may have a role in normal lung healing and gain therapeutic benefit for patients with lung fibrosis.
Keywords: idiopathic pulmonary fibrosis; lung fibrosis; extra-cellular matrix; macrophages; lysosomes